Relaxation Dynamics of Biomass-Derived Copolymers With Promising Gas-Barrier Properties - Sanz, Alejandro; Linares, Amelia; García-Gutiérrez, Mari Cruz; Nogales, Aurora; Paszkiewicz, Sandra; Zubkiewicz, Agata; Szymczyk, Anna; Ezquerra, Tiberio A. (Frontiers in Chemistry, 2022)
This article presents an experimental study on the relaxation dynamics of a series of random copolymers based on bio-friendly comonomers with interesting gas barrier properties. We analyze the relaxation response in the glassy and ultraviscous regime of poly(trimethylene furanoate/sebacate) random copolymers via dielectric spectroscopy. We report lower values of dynamic fragility (a dimensionless index introduced in 1985 (Angell, 1985)) in comparison to popular polyesters widely used in industry, such as poly(ethylene terephthalate), suggesting that the amorphous phase of these furanoate-based polyesters adopt an efficient chain packing. This is consistent with their low permeability to gases. We also discuss on different equations (phenomenological and theory-based approaches) for fitting the temperature-evolution of the alpha relaxation time.